Acetabular de-escalation in hip revision - Rivera, Fabrizio; Bardelli, Alessandro; Maniscalco, Pietro; Giolitti, Andrea (Acta Biomedica Atenei Parmensis, 2020)
Background: The idea of ‘‘de-escalation’’ (DE) indicates an arthroplasty revision performed by changing a revision component by a primary component. Aim of this study is to verify if this technique can represent an option in case of cage or ring failure. Methods: We observed five cases of revision hip cage loosening with complete allograft consolidation. This group of patients were revised with use of a primary cup and were specifically followed in ours institutions offices. Patients were clinically and radiologically followed every 6 months for the next two years and then annually Results: At final follow-up (15-2 years, mean 6 years) four patients (80%) showed a good recovery of their levels of activity. The mean Harris hip score improved from 20 points (range,7-38 points) preoperatively to 48 points (range, 16-88 points). At final radiological follow-up acetabular components were radiographically stable at the last follow-up. One patient (20%) at two years follow-up, was unable to walk without crutchies due to hip pain. X-rays showed cup loosening in all three zones. Patient was dissatisfied. Primary cup was revised with a Burch Schneider cage. Conclusions: De-escalation technique is a surgical option to consider in case of young patients, limited number of previous revisions and more than three years survivorship of loosened acetabular cage.